The Effectivity of Direct Learning Models Assisted Number Staircase Media in Mathematics Learning for First Grade Students at Elementary School - Marlina Buritta; Mas’ud Badolo; Idha Novianti (PT ARRUS Intelektual Indonesia, 2023)
This study focuses on knowing the effectivity of direct learning models assisted number staircase media in mathematics learning for first grade students of SD, and describing the learning outcomes before and after being taught using the direct learning model models assisted number staircase media. This study uses a quantitative approach with a pre-experimental design one-group pretest-posttest model. The population in this study amounted to 73 students at SD Negeri 7 Sa'dan. The sampling technique in this study uses probability sampling with a cluster random sampling model. Data collection techniques are counting ability tests, observation of student activities. Based on the data analysis obtained the value of sig. (2-tailed) 0.000 <0.05 it was concluded that the direct learning model assisted by assisted number staircase media had an effect on the learning outcomes of the first graders of SD Negeri 7 Sa'dan. From the N-gain analysis, the N-gain value is 0.64865 and is included in the effective category.